CHARACTERIZING AN UNSTABLE MOUNTAIN SLOPE USING SHALLOW 2D AND 3D SEISMIC TOMOGRAPHY - Heincke B.; Maurer H.; Green A.G.; Spillmann T.; Willenberg H.; Burlini L. (My University, 2006)
As transport routes and population centers in mountainous areas expand, risks associated with rockfalls and rockslides grow at an alarming rate. As a consequence, there is an urgent need to delineate mountain slopes susceptible to catastrophic collapse in a safe and noninvasive manner. For this purpose, we have developed a 3D tomographic seismic refraction technique and applied it to an unstable alpine mountain slope, a significant segment of which is moving at 0.01-0.02 m/year toward the adjacent valley floor. First arrivals recorded across an extensive region of the exposed gneissic rock mass have extraordinarily low apparent velocities at short (0.2 m) to long (> 100 m) shot-receiver offsets. Inversion of the first-arrival traveltimes produces a 3D tomogram that reveals the presence of a huge volume of very-low-quality rock with ultralow to very low P-wave velocities of 500-2700 m/s. These values are astonishingly low compared to the average horizontal P-wave velocity of 5400 m/s determined from laboratory analyses of intact rocks collected at the investigation site. The extremely low field velocities likely result from the ubiquitous presence of dry cracks, fracture zones, and faults on a wide variety of scales. They extend to more than 35 m depth over a 200 X 150-m area that encompasses the mobile segment of the mountain slope, which is transected by a number of actively opening fracture zones and faults, and a large part of the adjacent stationary slope. Although hazards related to the mobile segment have been recognized since the last major rockslides affected the mountain in 1991, those related to the adjacent low-quality stationary rock mass have not.